2019
DOI: 10.1038/s41598-019-55649-y
|View full text |Cite
|
Sign up to set email alerts
|

On the first evidence of exchange-bias feature in magnetically contrasted consolidates made from CoFe2O4-CoO core-shell nanoparticles

Abstract: Hetero-nanostructures based on magnetic contrast oxides have been prepared as highly dense nanoconsolidates. Cobalt ferrite-cobalt oxide core-shell type nanoparticles (NPs) were synthesized by seed mediated growth in polyol and subsequently consolidated by Spark Plasma Sintering (SPS) at 500 °C for a few minutes while applying a uniaxial pressure of 100 MPa. It is interesting to note that the exchange bias feature observed in the core-shell NPs is reproduced in their ceramic counterparts, or even attenuated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The polyol route synthesized core-shell nanoparticles (Fe2O3/Gd2O3 CSNPs) with gadolinium oxide (Gd2O3) encapsulating iron oxide (Fe2O3) were synthesized by Rajesh et al [60] examined their frequency-dependent dielectric dispersion and cobalt ferrite-cobalt oxide core-shell nano-particles were successfully synthesized by Martinez et al [61] through seedmediated growth in a polyol medium.…”
Section: Semiconductor Nanoparticles (I) Cadmium Selenide Nanoparticl...mentioning
confidence: 99%
“…The polyol route synthesized core-shell nanoparticles (Fe2O3/Gd2O3 CSNPs) with gadolinium oxide (Gd2O3) encapsulating iron oxide (Fe2O3) were synthesized by Rajesh et al [60] examined their frequency-dependent dielectric dispersion and cobalt ferrite-cobalt oxide core-shell nano-particles were successfully synthesized by Martinez et al [61] through seedmediated growth in a polyol medium.…”
Section: Semiconductor Nanoparticles (I) Cadmium Selenide Nanoparticl...mentioning
confidence: 99%
“…Spherical nanoparticles, with their isotropic geometry, exhibit a uniform distribution of exchange interactions across the entire surface [23,26]. However, due to the symmetrical nature of spheres, the distribution of uncompensated spins, which are critical for the exchange bias, is relatively uniform, resulting in moderate exchange bias effects [27]. The nanoparticles such as nanorods, nanodiscs, or nanocubes display a much more complex interaction [28].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In addition, thanks to the progress in controlled chemical synthesis and to the advances in technical instruments for the study of the structural-morphological and magnetic properties, it is possible to explore EB in a wide range of nanoparticle systems, such as doubly inverted nanoparticles, 13,14 core/shell nanoparticles with different compositions, 15,16 and nanocomposites. 17,18 The experimental results on nanocomposites based on the hexaferrite hard/so ferrite interface have shown that the magnetic properties depend on the hard/ so phase ratios. 19,20 López-Ortega et al gave a detailed study of the magnetic behaviour and applications of exchange coupled bimagnetic hard/so and so/hard magnetic core/shell nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The cooling eld dependence of the exchange bias eld and the coercivity in core/shell nanoparticles has been studied by several authors. 2,17,[21][22][23][24][25][26] In these studies, it has been observed that as the applied eld increases the exchange bias phenomena are increasing. This is attributed to the competition between the Zeeman energy and the exchange anisotropy energy for a range of applied elds.…”
Section: Introductionmentioning
confidence: 99%